Taxation and Economic Performance - Leibfritz, Willi (OECD Economics Department Working Papers, 1997)
This paper reviews the theoretical and empirical literature on the effects of taxation on economic performance, adds marginally to the empirical literature, and draws conclusions for tax policy in OECD countries. Key issues covered are how, in open OECD economies, taxes may have affected economic performance via their effects on capital and labour markets, and on human capital formation. Perhaps the most important policy conclusion that emerges is that the increased integration of OECD capital markets limits the scope for using tax incentives to raise domestic savings and investment, which suggests that the tax burden in the future will have to fall increasingly on labour as the less mobile factor of production. With labour taxes having already increased sharply in recent years, contributing to a reduced demand for labour, greater labour-market flexibility is required to facilitate employers' passing labour taxes on to reductions in real wages so as to reduce labour costs; while ...